2018
DOI: 10.1128/aem.01393-18
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Bacillus thuringiensis Cry1Ab and Cry1Fa Toxicity to Spodoptera frugiperda by Domain III Mutations Indicates There Are Two Limiting Steps in Toxicity as Defined by Receptor Binding and Protein Stability

Abstract: Cry1Ab and Cry1Fa toxins are environmentally safe insecticides that control important insect pests. is an important maize pest that shows low susceptibility to Cry1A toxins, in contrast to Cry1Fa, which is highly active against this pest and is used in transgenic maize for control. The β16 region from domain III of Cry1Ab has been shown to be involved in interactions with receptors such as alkaline phosphatase (ALP) or aminopeptidase (APN) in different lepidopteran insects. Alanine-scanning mutagenesis of amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
(51 reference statements)
5
14
1
Order By: Relevance
“…Recent work showed that S. frugiperda is less sensitive to Cry1Ab since Cry1Ab protoxin is highly unstable against S. frugiperda gut proteases and also because Cry1Ab showed a low binding affinity for the receptors located in the brush border membrane (BBM) of S. frugiperda midgut cells (39). Here, we show that PxHsp90 also increased Cry1Ab and Cry1Ac toxicity to S. frugiperda .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work showed that S. frugiperda is less sensitive to Cry1Ab since Cry1Ab protoxin is highly unstable against S. frugiperda gut proteases and also because Cry1Ab showed a low binding affinity for the receptors located in the brush border membrane (BBM) of S. frugiperda midgut cells (39). Here, we show that PxHsp90 also increased Cry1Ab and Cry1Ac toxicity to S. frugiperda .…”
Section: Discussionmentioning
confidence: 99%
“…Another area that has recently been demonstrated to be susceptible to improvement by site directed mutagenesis is the β sheet 16 in Domain III. A study of alanine substitution in Cry1Ab [97] performed on this area rendered mutants S509A, V513A, and N514A, which showed an increase in toxicity toward Spodoptera frugiperda of more than 9.5-, 12.7-, and 51-fold, respectively. As N514 was the most relevant position experiencing toxicity enhancement in β-16, saturation mutagenesis was performed at this position (N was changed for any of the other 19 amino acids).…”
Section: Evolution By Site-directed Mutagenesismentioning
confidence: 99%
“…These results indicate that Cry1Ab toxicity is limited by some additional mechanisms, other than receptor binding, in the wild type DH19 larvae. It was reported that the lack of toxicity of Cry1Ab to an S. frugiperda population from México correlated with enhanced toxin degradation by midgut proteases and also with reduced receptor binding [32]. In addition, it is still possible that an additional Cry1Ab receptor is expressed in the Hi5 cells but not in S. frugiperda larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of T. ni, Cry1Ac variants that could bind to the TnCad protein were selected by continuous evolution, and it was found that the Cry1Ac variants that were able to bind to TnCad were also able to counter resistance of T. ni insects linked to ABCC2 mutations [40]. In addition, Cry1Ab domain III mutants were shown to increase the toxicity of Cry1Ab to different S. frugiperda strains, which was correlated with their increased binding to SfCad receptor [32]. Overall our results show that S. frugiperda cadherin is not a functional receptor of Cry1Fa and Cry1Ab toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation